Women’s Awareness on the Law on Anti-Violence Against Women and their Children - Caparas, Mary Ann E.; Amparado, Mauro Allan P. (JPAIR Multidisciplinary Research, 2012)
The Republic Act No. 9262 otherwise known as Anti-Violence against Women and Their Children Act of 2004 provides the legal framework of the country’s effort to address violence committed against women and children in keeping with the fundamental freedom guaranteed under the Constitution and the Provisions of the Universal Declaration of Human Rights. This study determined the awareness on Anti-Violence against Women and their Children Law among women of Village Looc, Mandaue City, Philippines in 2011. This study utilized the descriptive-correlational design. The respondents were 96 women who were selected through purposive sampling with the inclusion criteria that they must be at least 16 years old and living with a partner. Majority of the respondents were 25-65 years old, single with live-in partner, has 0-3 children, high school graduates and belonged to the low monthly income bracket. Most of the respondents expressed that they have acquired awareness on intimate partner violence from watching television. Majority of the respondents were aware of the intimate partner violence in RA 9262. There was a significant relationship between the modes of Information, Education and Communication (IEC) and level of awareness of the respondents on RA 9262. This study concludes that full awareness on RA 9262 through the modes of IEC is necessary to ensure protection of women and their children.